Acquisition of semantic information from discourse: Effects of repeated exposures - Frederiksen, Carl H. (Journal of verbal learning and verbal behavior, 1975)
When subjects are asked to recall the semantic content of a text, they typically produce conceptual and relational responses which do not simply reproduce text content. These responses include overgeneralized and inferred concepts and semantic relations. Two process interpretations of these responses were considered, one in which the responses reflect processes of adjustment during acquisition to conditions of information overload, and a second in which they reflect processes occurring during recall. The two alternative interpretations were found to lead to opposite predictions concerning effects of repeated exposures to a text on frequencies of these responses and on correlations of these responses with amount of information reproduced from a text. The results were entirely consistent with the predictions derived from the first interpretation.